TOXICITY STUDY OF CO2 RELEASE IN BIOGAS PROCESS USING COMPUTATIONAL FLUID DYNAMICS MODELING - YAHYA, AHMAD FAHMY (Universiti Teknologi PETRONAS, 2013)
Biogas processing technologies have been widely applied in industries due to the limitation of non-renewable energy as a source of energy. Together with the biogas production, the emission of carbon dioxide gas from the product also brings the major concern on how safe the carbon dioxide gas concentration from the biogas industry could be. In fact, accidental release of carbon dioxide may cause severe damage and losses during the biogas production. Example of biogas production is landfill gas (LFG) that produces by anaerobic condition through the degradation of municipal solid waste by microorganism. The ability to predict foreseeable accidental scenarios and investigate their consequences is a fundamental aspect in the assessment of the risk of a process or technology. However, due to the limited operational experience in biogas, the process to identify the hazard especially toxicity associated with a larger scale process like biogas become more difficult and complicated. This paper presents an early investigation on how the carbon dioxide gas will react and disperse to the atmosphere due to the leaking in biogas process. Besides, the most important part for this project is to find out the toxicity safe distance on carbon dioxide release in biogas process base on its concentration. Thus, a Computational Fluid Dynamic (CFD) modeling is used to simulate the dispersion behavior of biogas from pressurized release into the atmosphere. CFD is the well-known tool used to investigate the behavior of released substance especially liquid and gas. CFD also equipped with a branch of fluid mechanics that involve algorithm and numerical method to solve the problem related with the fluid flow. In comparison with the natural gas, biogas will shows higher concentration of carbon dioxide because of the low carbon dioxide content in the natural gas. Hence, it proof that biogas is more toxicity than natural gas in term of carbon dioxide release.